Code of ethics for electronic media in Pakistan - Ahmad, Awais (Technium Social Sciences Journal, 2022)
“Who will watch the watchdog” This praise became popular in Pakistan when Geo, one of Pakistan’s most-watched television news channels in Pakistan, has many times violated codes of ethics that were proposed by Pakistan Electronic Media Regulatory Authority (PEMRA) (Pakistan Voice, 2012, p. 2-6). Media plays an important role in our daily lives, as its basic function is to inform, educate and entertain. Today?s world media is getting more and more power because it plays a role of watchdog on politicians, governments, judiciary and our actions and can quickly inform masses and disseminate information across the globe. Therefore, freedom of media is very essential if it plays a constructive and significant role for people living in a democratic country like Pakistan. But if the press itself is not free then how can it play a constructive role or can raise voice for the rights of the citizens. Edmund Burkey (1787) stated that media is the fourth-pillar of the state. He termed it fourth-pillar because of its constructive role in our lives, the press or media can only perform its sacred duties of the fourth estate if it is free and independent in covering different aspects of life, whether it is politics, education, health, religion, war zone or any other important topics. Most importantly, it is only possible if the job is done professionally, ethically and with full responsibility.